2019
DOI: 10.1111/tbj.13356
|View full text |Cite
|
Sign up to set email alerts
|

Delayed‐immediate hybrid breast reconstruction—Increasing patient input and precision in breast reconstruction

Abstract: The benefits of breast reconstruction via free tissue transfer with simultaneous implant placement, that is, hybrid breast reconstruction, in select patients are well‐known. Challenges exist, however, and are related to proper implant selection as well as postoperative mastectomy skin necrosis. Here, the authors present an approach that increases reconstructive precision while minimizing postoperative mastectomy skin necrosis. A retrospective analysis of patients who underwent immediate prepectoral tissue expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
10
0
4
Order By: Relevance
“…19 Furthermore, when examining two-stage reconstruction, studies have shown that the majority of complications, such as surgical-site infection, wound healing complications, and reconstructive failure, occurred in the first stage with tissue expander placement. 8,[20][21][22] These findings are thought to be attributable to the placement of the expander or implant in a hypovascular field with a large amount of dead space. 12 In addition, the combination of two separate surgical teams in the first reconstructive stage may contribute to the increased rates of complications seen in the staged cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, when examining two-stage reconstruction, studies have shown that the majority of complications, such as surgical-site infection, wound healing complications, and reconstructive failure, occurred in the first stage with tissue expander placement. 8,[20][21][22] These findings are thought to be attributable to the placement of the expander or implant in a hypovascular field with a large amount of dead space. 12 In addition, the combination of two separate surgical teams in the first reconstructive stage may contribute to the increased rates of complications seen in the staged cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used for staged free-flap breast reconstruction was similar to techniques described previously. [6][7][8][9] In patients undergoing prepectoral reconstruction, acellular dermal matrix was used to drape the anterior surface of the expander before securing the device to the chest wall. During partial submuscular placement, a sling of acellular dermal matrix was used to cover the inferior edge of the device.…”
Section: Methodsmentioning
confidence: 99%
“…At our institution, patients are evaluated for delayed or staged free-flap breast reconstruction if they are expected to undergo postmastectomy radiation therapy, have significant medical comorbidities, are uncertain about their definitive choice for reconstruction, and/or have tenuous skin flaps at the time of mastectomy. The technique used for staged reconstruction is similar to those previously described 3,4,18,19 . In patients undergoing prepectoral reconstruction, acellular dermal matrix (ADM) is draped over the anterior surface of the expander before securing the device to the chest wall.…”
Section: Methodsmentioning
confidence: 99%
“…The technique used for staged reconstruction is similar to those previously described. 3,4,18,19 In patients undergoing prepectoral reconstruction, acellular dermal matrix (ADM) is draped over the anterior surface of the expander before securing the device to the chest wall. During partial submuscular placement, a sling of ADM is used to cover the inferior edge of the device.…”
Section: Methodsmentioning
confidence: 99%
“…‚delayed-immediate' Vorgehen. Hierbei wird nach Mastektomie zunächst ein präpektoraler Gewebeexpander eingelegt und erst in einem zweiten Schritt die Hybridrekonstruktion mittels freiem Gewebetransfer vom Abdomen mit gleichzeitiger Implantatplatzierung vorgenommen [39]. Die Einlage eines Gewebeexpanders und Modifizierung der Füllmenge kann eine Reduktion der Rate an Mastektomiehautnekrosen bewirken [40].…”
Section: Zeitpunkt Der Implantatplatzierungunclassified